AN ANALYSIS OF SIMILE FIGURES OF SPEECH IN KATY PERRY’S SONG “FIREWORK” - Butar-Butar, Silvia; Nasution, Jamaluddin; Arnelita, Tia; Manullang, Riyanti Agni Hotthere; Hutauruk, Gracia Anggelika (Smart Education, 2025)
Abstract: This study examines the employment of simile in Katy Perry's song